Blancanieves retextualiza Branca de Neve: análise da multimodalidade na linguagem cinematográfica - Coelho, Glaucimere Patero (2020)
The present dissertation aims to reframe the studies of the retextualization process, which is established from the interrelationship of multimodal codes. Drawing on the theoretical assumptions of Textual Linguistics (henceforth TL) with a socio-cognitive interactional basis, focusing on the phenomena of intertextuality and referencing, we seek to undertake a comparative analysis between two filmic texts present in the film industry. The motivating corpus consists of the basic text, which is the Walt Disney classic Snow White and the Seven Dwarfs (2009) in an animation format, and the film Blancanieves (2012) produced by the Spanish filmmaker Pablo Berger, who retextualized the work for the silent cinema. As it was pointed out, in order to support the present dissertation, textual linguistic scholars are taken as theoretical contribution, among them Koch (2009, 2011), Mondada & Dubois (2003), Marcuschi (2008, 2010) and Cavalcante (2011). In addition to the methodological theoretical path, an interdisciplinary dialogue is traced, based on the Social Semiotics (HODGE; KRESS, 1988; VAN LEEUWEN, 2005; KRESS, 2010) and supported by some categories of the Grammar of Visual Design by Kress and van Leeuwem (2006[1996]). In this regard, we justify the convenience of analyzing the filmic text as it promotes the investigation of multimodality, especially with regard to the elaboration of structural and compositional elements. Our results showed that the interdisciplinary nature of TL allowed the development of an analytical theoretical framework involving multimodality along with linguistic, textual, discursive and cognitive aspects. In addition, the analyzes undertaken indicated that retextualization is constitutively an intertextual process, guided by the construction of referents that emerge from a discursive world distant from the base text, in historical, ideological and cultural terms, therefore, the retextualization is situated in continuum of more distancing than approximation with the base text, which configures a recontextualization promoted by the retextualizer.